THE ROLES OF VISUAL ELEMENTS IN ENGLISH SPOKEN MEDIA FOR EFL TEACHING SPEAKING: A LITERATURE REVIEW - luluk setyowati (STKIP PGRI Jombang, 2021)
Speaking is the ability to say a sentence to communicate or articulate intentions, ideas, beliefs, and feelings that are formed and organized in a suitable way for the listener's needs so that what is expressed can be understood. Someone must communicate orally in spoken communication, efficiently and transmitting information to the listener or other so that the audience can comprehend the speaker's stated goals and objectives. In Indonesia, the problems faced by students regarding their speaking performance is related to not only their linguistic and personality factors, but also the types of classroom tasks provided by the teachers. Thus, this section suggests that teachers have an important role in fostering learners ability to speak English well. To address this issue, teacher can use audio visual media. Visual elements contained in the media, can help in advancing the student’s language aptitude. The use of the visual content, particularly that of video, assists the learning in their academic endeavours.